1993
DOI: 10.3109/13813459308998131
|View full text |Cite
|
Sign up to set email alerts
|

Peptide mapping of mammalian brain protein h3in subsets of tissues and ligand binding studies

Abstract: In this report the structure of the novel polypeptide h3, isolated from subsets of tissues of a single species, and the structural similarity between interspecies h3 were investigated by peptide mapping of enzymatic and chemical cleavage fragments of h3 in one-dimensional SDS-PAGE; the peptide maps were commented on in comparison with the known sequence of 21 kDa protein, a h3-like ox brain protein. The following results were obtained: peptides generated by chymotrypsin, protease XX, BNPS-skatole and CNBr clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The similar behaviour in urea-gelchromatography and urea-gradient-PAGE of the different species-h3 shows that they do not only share a common backbone structure (Bollengier et al, 1993, Seddiqi et al, 1994, but also conformational properties.…”
mentioning
confidence: 78%
“…The similar behaviour in urea-gelchromatography and urea-gradient-PAGE of the different species-h3 shows that they do not only share a common backbone structure (Bollengier et al, 1993, Seddiqi et al, 1994, but also conformational properties.…”
mentioning
confidence: 78%
“…When comparing the three mammalian proteins, three different amino acids are found in five positions: four positions are situated at the N-terminal part of the molecule (residues 19-32) and one position is located at the C-terminal region (residue 128); thus, the N-terminal part is the one most variable. Considering that we were able to demonstrate phosphatidylethanolamine-binding property for B. taurus 21-kDa protein (Bernier et al 1986), but not for H. sapiens h3 (Bollengier et al 1993), one might speculate that the observed N-terminal variability could account for functional differences between the members of the 21-23-kDa family. On the contrary, the region constituted by residues 60-126 appears to be better conserved than the N-and C-terminal sequences.…”
Section: Discussionmentioning
confidence: 99%
“…By immunoblotting, h3 was encountered in brain but also in muscle and liver from Homo sapiens, Bos taurus, Rattus norvegicus, and Gallus gallus (Bollengier et al 1983;Bollengier and Mahler 1988). Moreover, h3 isolated from different tissues in a single species appeared to be identical, whereas it revealed slight structural differences when purified from analogous tissues in different species (Bollengier et al 1993).…”
Section: Introductionmentioning
confidence: 97%